Energy analysis of scraped surface heat exchanger during Kheer making - Jain, Sapna; Karthikeyan, S.; Purohit, Pankaj; Bhadania, A. G.; Agrawal, A. K.; Sahu, C. (Indian Journal of Dairy Science, 2022)
Kheer is a cereal based sweetened and concentrated milk confection, very well-liked in India. The present investigation was undertaken to study the energy consumption of the developed batch type scraped surface heat exchanger (SSHE) for kheer making. The kheer was prepared by using SSHE at different levels of steam pressure (1.0, 1.5 and 2.0 kg/cm2), scraper speed (10, 20 and 30 rpm) and batch size (10, 15 and 20 kg). The thermal and electrical energy consumptions were determined. The rate of evaporation increased with increase in operating variables. The average rate of evaporation ranged from 11.84 to 25.65 kg water evaporated/h. The specific steam consumption by the SSHE during kheer making ranged between 1.568 and 1.702 kg steam/kg of water evaporated under different operating conditions of the machine. The total heat losses during manufacture of kheer in SSHE ranged from 12.9 to 18.9 %.Â  The electrical power consumption of the machine during manufacturing of kheer varied from 230.1 to 260.5 W.